Social-economic Analysis of Physical Integration between Brazil and Peru: Focus for the Regions Linked to the Interoceanic Highway - Arevalo, Jorge Luis Sanchez; Merlo, Edgard Monforte (International Journal of Economics and Financial Issues, 2020)
The objective of the study was to estimate the impact of the interoceanic highway construction on trade facilitation between Brazil and Peru, especially in the states linked to the highway. The methodology starts from a panel data econometric approach. The results indicate a positive impact of highway construction on trade facilitation for the linked states. On the other hand, a positive relationship was found between greater distance and trade flow, which is justified by the fact that the more developed states and, therefore, with greater trade flow are located farther than the border of both countries. Keywords: Physical Integration; Border, flow of trade; Gravitational model. JEL Classifications: F1, F15, H54 DOI: https://doi.org/10.32479/ijefi.9313